The Effect Of Incentives And Work Motivation On Employee Performance At PT. Indomarco Prismatama West Jakarta Area 1 - Aisyah, Elisa Nur; Sularmi, Lili (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2025)
The purpose of this study is to determine the effect of incentives and work motivation on employee performance at PT. Indomarco Prismatama Area West Jakarta 1, both partially and simultaneously. The method used is associative quantitative research. The sampling technique applied is saturated sampling, resulting in a total of 60 employees as the research sample. Data analysis includes validity testing, reliability testing, classical assumption testing, multiple regression analysis, determination coefficient analysis, and hypothesis testing. The analysis results indicate that the multiple regression equation is Y = 54.018 + 0.724X1 + 0.523X2, with an Adjusted R Square value of 0.919. This result implies that 91.9% of the variance in employee performance is influenced simultaneously by incentives and work motivation, while the remaining 8.1% is affected by other factors.